The Impact of Product Attributes, Price, Place, Advertising, and Sales Promotion: A Case of Kids Shampoo in Indonesia - Adelina Proboyo; Bram Imantaka Kusuma (Petra International Journal of Business Studies, 2019)
Kids shampoo has been the main driver of growth for the slow-growing baby and child hair care industry in Indonesia. Knowing this phenomenon, Company A launched Product X, a kids shampoo product, in 2016. The purpose of this research is to do a gap analysis between the perception and the expectation of intrinsic and extrinsic product attributes, sales promotion, and place. Prior to the gap analysis, 109 data is collected through online questionnaires and then analyzed using a multiple regression analysis to know the impact of intrinsic and extrinsic product attributes, price, place, advertising, and sales promotion on purchase intention. The result shows that intrinsic and extrinsic product attributes, sales promotion, and place influence purchase intention significantly, while price and advertising are not significant. From the gap analysis, the perceived performance of Product X on four significant elements is lower than the expectation.